Thoughts and notions : High beginning reading practice with answers - Lee, Linda; Bushby, Barbara; Lê Ngọc Phương Nam (Tp.HCM : Nxb Trẻ, 2000)
Sách gồm những bài tập về suy nghĩ và khái niệm trong việc luyện đọc tiếng Anh.
Keywords: Anh ngữ; English language; Reading skills; English language -- Reading -- Study and teaching